2019
DOI: 10.1016/j.scitotenv.2019.02.457
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of elemental mercury by biogenic Se nanoparticles in soils of varying salinity

Abstract: Salinity can be a significant environmental stress which can govern the fate of nanoparticles in the environment as well as other factors such as pH, natural organic matter and minerals. In this research, the effects of salinity on the behaviour of biogenic selenium nanoparticles (BioSeNPs) and consequences for elemental mercury (Hg 0 ) immobilization in soil and soil solutions were investigated. It was found that homoaggregation and sedimentation of BioSeNPs were enhanced significantly with increasing salinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Further investigations are needed to monitor the behavior of Se-NPs in different environments including agricultural soils, waters, and farm animals. Se-NPs have already been used in the remediation of soils and waters that were contaminated with heavy metals like mercury [225][226][227]. This work confirmed that soils and groundwater contaminated with elemental mercury could be remediated via biogenic Se-NPs based on mechanisms like the immobilization of elemental mercury [226,227], applied hetero-aggregation of soil particulate organic matter [225], applied biofilm-coated quartz sand [228], and applied goethite colloids [138] in the presence of Se-NPs [64].…”
Section: Are Selenium and Nano-selenium Emerging Pollutants?supporting
confidence: 56%
See 1 more Smart Citation
“…Further investigations are needed to monitor the behavior of Se-NPs in different environments including agricultural soils, waters, and farm animals. Se-NPs have already been used in the remediation of soils and waters that were contaminated with heavy metals like mercury [225][226][227]. This work confirmed that soils and groundwater contaminated with elemental mercury could be remediated via biogenic Se-NPs based on mechanisms like the immobilization of elemental mercury [226,227], applied hetero-aggregation of soil particulate organic matter [225], applied biofilm-coated quartz sand [228], and applied goethite colloids [138] in the presence of Se-NPs [64].…”
Section: Are Selenium and Nano-selenium Emerging Pollutants?supporting
confidence: 56%
“…Se-NPs have already been used in the remediation of soils and waters that were contaminated with heavy metals like mercury [225][226][227]. This work confirmed that soils and groundwater contaminated with elemental mercury could be remediated via biogenic Se-NPs based on mechanisms like the immobilization of elemental mercury [226,227], applied hetero-aggregation of soil particulate organic matter [225], applied biofilm-coated quartz sand [228], and applied goethite colloids [138] in the presence of Se-NPs [64]. Further investigations are needed to monitor the behavior of Se-NPs in different environments including agricultural soils, waters, and farm animals.…”
Section: Are Selenium and Nano-selenium Emerging Pollutants?mentioning
confidence: 99%
“…There is a tremendous amount of literature available on the biosynthesis of SeNPs. 80–87 Biological agent mediated synthesis is easy as this does not require special apparatus and conditions. These biological reagents include bacteria, fungi, algae, protein molecules and plant extracts.…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…It is reported that biological extracts act as bioreducing agents, as well as stabilizers for nanoparticles. There is tremendous amount of literature available on the biosynthesis of SeNPs [80][81][82][83][84][85][86][87] . The biological agent mediated synthesis is easy as this does not require special apparatus and conditions.…”
Section: Biogenic Reductionmentioning
confidence: 99%
“…At nonartisanal mining sites, a positive correlation between TGM and soil THg can be observed ( r 2 = 0.82, p < 0.01), suggesting that TGM mainly originated from the in situ emission of Hg 0 from the soil. It is likely the elevated soil TSe at nonartisanal mining sites can reduce the bioavailability of soil Hg or the emission of Hg 0 from the soil, through the formation of less soluble HgSe in soil. At artisanal mining sites, however, we did not observe any clear correlation between soil TSe and BAFs of Hg in rice tissues (Figure B). Unlike nonartisanal mining sites, no significant correlation between TGM and soil THg was observed at artisanal mining sites, suggesting that the TGM was not mainly emitted from soil, but directly from artisanal mining activities.…”
Section: Discussionmentioning
confidence: 76%